The Electron and Hole Effective Masses in Thermal Silicon Dioxide Determined from the Perspective of a Semiconductor - Chanana, Ravi Kumar (Transactions on Engineering and Computing Sciences, 2023)
Three experimentally determined parameters of valence band to oxide conduction band offset, the bandgap of 4H-SiC, and the longitudinal electron effective mass in 4H-SiC, coupled with the universal mass-energy equivalence relation, facilitate the determination of the electron and hole effective masses in thermal silicon dioxide of a metal-oxide-semiconductor (MOS) device without prior knowledge of any of the oxide masses.